2010
DOI: 10.1063/1.3518486
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domain-wall depinning with reduced current density by short pulse rise time

Abstract: The depinning probability of magnetic domain walls at constrictions by current pulses depends on the external magnetic field and on the temporal shape of current pulses. We investigate the depinning of domain walls in permalloy nanowires in dependence of the rise time of a current pulse. We observe a change in the depinning probability when varying the pulse rise time and the pulse amplitude at a constant magnetic field. The experiments reveal that the current density for domain-wall depinning can be strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…3,[13][14][15][16] The model simulations presented here show for all of them that the temperature increase due to the Joule heating did not result in the temperature exceeding the Curie temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[13][14][15][16] The model simulations presented here show for all of them that the temperature increase due to the Joule heating did not result in the temperature exceeding the Curie temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Section III C studies a nanowire with a notch-like constriction (triangular shape removed from the wire on one side only) that is placed on a silicon nitride substrate of 100 nm thickness (as in Ref. [13][14][15]. The same system is studied in Sec.…”
Section: -10mentioning
confidence: 99%
“…For instance, it was found that adjusting the rise time of the applied pulse current will amplify the motion of a DW. 4,5 It has also been shown that when the applied current density is higher than a critical value, a transverse DW undergoes a chirality flipping, 6,7 the phenomenon is known as Walker breakdown. High data density design implies that the nanowires will be placed very close to each other.…”
mentioning
confidence: 98%
“…Moreover, the DWs in in-plane materials are forced to rotate along the in-plane orientation, which is also known as the Néel configuration. DWs in in-plane materials have been shown to be able to move with a high speed under the application of current 4 5 . However, it has also been shown that the motions of DWs within in-plane materials are often not reproducible 6 .…”
mentioning
confidence: 99%